Undiagnosed neurologic disease in refractory chronic pelvic pain: High yield in screen-positive patients - Talia Denis; Dyer Pettijohn; Elise J.B. De; Charles E. Argoff (Continence)
Introduction:: Primary management of chronic pelvic pain depends on identifying and addressing its underlying etiologies. The prevalence of neurological conditions in the setting of chronic pelvic pain is poorly documented. In this study, we actively screened patients with chronic pelvic pain within our combined Urology/Urogynecology/Neurology Pain Management specialty clinics for multidisciplinary pelvic symptomatology, including neurologic, and, if present, facilitated multidisciplinary assessment of the patient. Methods:: A standardized, systematic neurological history and physical was conducted when screening suggested a structural or functional nervous system disorder. Subsequent neurological testing was tailored to the clinical findings. Results:: Of 188 patients who screened positive for neurological symptoms and signs and initiated combined evaluation, 126 (67%) completed recommended neurological evaluation and testing. Of the 126 who completed workup, 92 (73%) were found to have objective evidence of a neurological disorder, of which 77 (84%) were new diagnoses. The most common diagnoses included small fiber neuropathy, large fiber neuropathy, lumbosacral radiculopathy, and severe spinal stenosis. Conclusion:: Neurologic disease is prevalent in people with chronic pelvic pain who have neurologic symptoms and signs. Most of the neurologic diagnoses in this study were previously unidentified; thus, many patients had experienced neurodiagnostic delay. Screening for neurologic symptomatology is recommended in patients with chronic pelvic pain to facilitate diagnostic accuracy.